احکاماتِ نکاح پرمولانا سیدابوالاعلیٰ مودودی ؒکے بالاستیعاب تحقیقی مطالعہ کاجائزہ: A Review of the Research study commissioned by Maulana Syed Abu Ala Maududi on Nikah orders - Umar Farooq; Dr. Muqaddas Ullah (Al Manhal Research Journal, 2023)
Syed Abul Ala Maududi other services in religious affairs as well as jurisprudential services are also noteworthy in which there is a great writing regarding Nikah. Islam provides a comprehensive framework to address all aspects of life including family matters. And because of marriage, human beings have become morally protected, meaning they are saved from adultery and other immorality. Spouses are related on the basis of love and mercy, which makes civilization, lifestyle, culture and culture stronger. There are various duties on a man in marriage, it is the responsibility of the man to fulfill it, such as Amhar, Nalatafqa, etc. are worth mentioning. Marriage with all non-Muslims is prohibited for Muslim men and women. Those who are not People of the Book because they are so different from Muslims in their religion, their thoughts, their culture and their own ways that a true Muslim cannot match them with heartfelt love and unity of heart and soul. If, despite this difference, they are connected with each other, their marital relationship will not be a proper cultural relationship. Rather, it will become a mere sexual relationship. And either there will be no grace or mercy in it, or if there is, it will become useless instead of being useful for the Islamic civilization and civilization and for these Muslims themselves.